Synthesis of Branched Sugars and Chiral Aromatic Building Blocks Derived from Glycals - Maheshwari, Mittali; Hussain, Nazar (Synlett, 2025)
The transformation of sugar enolic ethers into branched sugars through C–H activation or cross-coupling reaction represents a compelling strategy in carbohydrate chemistry. These branched sugars serve as versatile intermediates for the synthesis of annulated sugars, which are key components in numerous biologically active molecules. This Account highlights various methodologies for the development of branched sugars, focusing on approaches utilizing glycals and alkenes through C–H activation and cross-coupling reactions. Additionally, it explores literature reports on the synthesis of chiral fused ring systems derived from functionalized glycals, offering insights into their significance in synthetic chemistry.1 Introduction2 Synthesis of Branched Sugars from Glycals3 Transformation of Branched Sugars to Annulated Sugars4 Conclusions
Keywords: glycals; C–H bond activation; cross-coupling; branched sugars; annulated sugars